Enhancing Thermal Comfort in Historic Buildings by Wind-Driven Ventilation Systems—A Case Study of the Praterateliers in Vienna - Aida Shayegani; Viera Joklova; Katarina Kristianova; Juraj Illes (Energies)
This study investigates the effectiveness of natural wind-driven ventilation systems in enhancing thermal comfort and energy efficiency within the context of Central European climates, specifically Vienna. By addressing the unique challenges posed by cultural heritage buildings, such as the Praterateliers’ Pavilions, this research highlights the role of sustainable ventilation strategies in mitigating urban overheating, which is exacerbated by climate change. A novel focus is placed on integrating windcatchers with passive systems like earth tubes and solar ventilation to reduce reliance on mechanical cooling and achieve lower carbon emissions while adhering to heritage preservation regulations. Using DesignBuilder simulations and future climate data (2020–2030), this research evaluates the thermal performance of key zones within the Praterateliers under different operational scenarios. The selected analysis period (May to September) captures the peak thermal stress conditions in Vienna, with wind rose diagrams and temperature characteristics providing insights into the ventilation potential during these months. The quantitative results demonstrate that cross-ventilation, combined with windcatchers and subterranean air exchange systems, improved thermal comfort metrics—such as predicted mean vote indices—by up to 30%, particularly in windward and leeward zones. These findings underscore the viability of non-invasive natural ventilation systems in achieving optimal thermal conditions, demonstrating an innovative yet preservation-friendly approach to sustainable architecture. This research not only advances the application of passive cooling strategies in heritage buildings but also provides scalable solutions for addressing urban overheating in modern constructions.